Prevalence of Intensive-care-unit-acquired Thrombocytopenia in a Tertiary Care Hospital in Sudan - Sara Rahama; Kamal Mirghani; Mustafa Hussein; Sami Menasri (Dr. Sulaiman Al Habib Medical Journal)
Thrombocytopenia is a common finding in patients admitted to the Intensive Care Unit (ICU). This can be attributed to the wide spectrum of comorbidities that affect homeostasis in these patients. The aim of this study was to estimate the frequency of thrombocytopenia among patients admitted to the medical ICU of Omdurman Military Hospital, Sudan. An observational descriptive hospital-based cross-sectional survey was conducted to calculate the prevalence of ICU-acquired thrombocytopenia among patients admitted to the medical ICU of Omdurman Military Hospital. Patients were excluded if they had a platelet count <150,000/mm3 upon admission or if their platelet count dropped below that level <5 days post-admission. Among 160 patients, 112 (70%) developed thrombocytopenia. The mean platelet count upon admission was 237,600 ± 4,600/mm3. The use of thromboprophylaxis, antibiotics, sedation, and mechanical ventilatory support was significantly correlated with the drop in platelet count (p < 0.05). The study is probably the first of its kind to draw attention to the magnitude of ICU-acquired thrombocytopenia in Sudan. The results showed a significant impact of the blood disorder in the critical care setting. Several factors have been associated with the abnormality. The development of thrombocytopenia can carry unfavourable outcomes in terms of morbidity and mortality. Therefore, the detection of this abnormal parameter needs a prompt response.